2015
DOI: 10.1186/s40635-015-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1-7) improves oxygenation, while reducing cellular infiltrate and fibrosis in experimental Acute Respiratory Distress Syndrome

Abstract: BackgroundThe renin-angiotensin system (RAS) plays a role in the pathogenesis of ARDS, Angiotensin II (Ang-II) contributing to the pathogenesis of inflammation and fibrogenesis. Angiotensin-(1-7) (Ang-(1-7)) may antagonize the effects of Ang-II. This study was aimed at evaluating the potential for Ang-(1-7) to reduce injury, inflammation and fibrosis in an experimental model of ARDS in the acute and late phases.MethodsMale Sprague Dawley rats underwent an instillation of 0.1 M hydrochloric acid (HCl, 2.5 ml/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 44 publications
2
95
0
Order By: Relevance
“…In this model of ALI, all tested TWs for Ang‐(1–7) showed some form of therapeutic benefit, in that they alleviated OA‐induced increases in permeability, inflammatory markers or haemodynamic alterations. This finding is in line with prior work in which we and others have recently demonstrated the therapeutic potential of Ang‐(1–7) for the treatment of experimental ALI (Klein et al , ; Li et al , ; Zambelli et al , ). Of the four different time windows tested, the best protection in terms of lung vascular barrier function, inflammatory and haemodynamic parameters was provided by a continuous infusion of Ang‐(1–7) starting at the time of injury and continuing until the end of the experimental period (TW2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this model of ALI, all tested TWs for Ang‐(1–7) showed some form of therapeutic benefit, in that they alleviated OA‐induced increases in permeability, inflammatory markers or haemodynamic alterations. This finding is in line with prior work in which we and others have recently demonstrated the therapeutic potential of Ang‐(1–7) for the treatment of experimental ALI (Klein et al , ; Li et al , ; Zambelli et al , ). Of the four different time windows tested, the best protection in terms of lung vascular barrier function, inflammatory and haemodynamic parameters was provided by a continuous infusion of Ang‐(1–7) starting at the time of injury and continuing until the end of the experimental period (TW2).…”
Section: Discussionmentioning
confidence: 99%
“…However, metabolism of AngII by ACE2 concomitantly leads to the generation of Ang‐(1–7), which counteracts many of the effects of the AngII‐AT 1 receptor axis by signalling through its own receptor, Mas. In previous work, we and others have provided experimental proof‐of‐principle demonstrating not only that exogenous Ang‐(1–7) exerts similar or even more pronounced protective effects as recombinant ACE2 or pharmacological blockade of AT 1 receptors respectively (Klein et al , ; Li et al , ; Zambelli et al , ), but also that the protective effect of AT 1 receptor blockade is largely attributable to an enhanced signalling via the Ang‐(1–7)/Mas axis (Klein et al , ). The cellular mechanisms underlying the protective effects of Ang‐(1–7) in ALI are still incompletely understood but are likely to involve endothelial barrier‐stabilizing effects via cGMP‐dependent and cAMP‐dependent pathways, given that inhibition of NO synthase by L‐NAME inhibited the barrier‐protective effect of Ang‐(1–7) in lung microvascular endothelial cells challenged by thrombin (Klein et al , ) and that Ang‐(1–7) increased intracellular cAMP levels (Liu et al , ), which can attenuate endothelial leak (Moore et al , ) and reduce inflammatory cell infiltration (Derian et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…74,86,87 Ang (1-7) infusion in murine experimental ARDS decreased the proinflammatory response, improved lung injury scores and lung function, and decreased cellular infiltrate in piglets with acid aspiration. 74,82 These beneficial effects are mediated by downregulation of the intracellular proinflammatory NFkB cascade and increased NO synthesis. 51 A randomized controlled trial of recombinant human ACE2 in humans with ARDS showed it decreased Ang II levels and proinflammatory mediators, and augmented plasmatic surfactant protein D, with no hemodynamic side effects.…”
Section: Angiotensin-converting Enzymes In Acute Respiratory Distressmentioning
confidence: 93%
“…73 In sheer contrast, activation of the Ang (1-7)/ACE2 axis inhibits ROS production, downregulates proinflammatory cytokine secretion, and has immunomodulatory tissue-protective features (see Box 2). 60,62,66,74…”
Section: Renin-angiotensin Systems and The Immune Systemmentioning
confidence: 99%